Definitions and Clinical Trial Design Principles for Coronary Artery Chronic Total Occlusion Therapies: CTO-ARC Consensus Recommendations. Issue 5 (2nd February 2021) - Ybarra, Luiz F.; Rinfret, Stéphane; Brilakis, Emmanouil S.; Karmpaliotis, Dimitri; Azzalini, Lorenzo; Grantham, J. Aaron; Kandzari, David E.; Mashayekhi, Kambis; Spratt, James C.; Wijeysundera, Harindra C.; Ali, Ziad A.; Buller, Christopher E.; et al.
Abstract : Over the past 2 decades, chronic total occlusion (CTO) percutaneous coronary intervention has developed into its own subspecialty of interventional cardiology. Dedicated terminology, techniques, devices, courses, and training programs have enabled progressive advancements. However, only a few randomized trials have been performed to evaluate the safety and efficacy of CTO percutaneous coronary intervention. Moreover, several published observational studies have shown conflicting data. Part of the paucity of clinical data stems from the fact that prior studies have been suboptimally designed and performed. The absence of standardized end points and the discrepancy in definitions also prevent consistency and uniform interpretability of reported results in CTO intervention. To standardize the field, we therefore assembled a broad consortium comprising academicians, practicing physicians, researchers, medical society representatives, and regulators (US Food and Drug Administration) to develop methods, end points, biomarkers, parameters, data, materials, processes, procedures, evaluations, tools, and techniques for CTO interventions. This article summarizes the effort and is organized into 3 sections: key elements and procedural definitions, end point definitions, and clinical trial design principles. The Chronic Total Occlusion Academic Research Consortium is a first step toward improved comparability and interpretability of study results, supplying an increasingly growing body of CTO percutaneous coronary intervention evidence. Abstract : Supplemental Digital Content is available in the text.